2021
DOI: 10.2147/rmhp.s327440
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol in Peripheral Blood Predicts the Severity and Prognosis in Patients with Liver Failure at 90 Days

Abstract: Objective:To investigate the cortisol level in peripheral blood in evaluating the severity and prognosis of patients with liver failure. Methods: A total of 211 inpatients with liver failure were enrolled in Beijing You 'an Hospital affiliated with Capital Medical University, from September 2018 to January 2020. They were divided into three groups according to the severity of liver failure: early-stage liver failure, medium-stage liver failure and end-stage liver failure. In all patients, peripheral venous blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the current research, prolactin and cortisol levels were an independent risk factor, while PV Diameter, MELD score, Child Score, and Ascities were independent variables impacting the prognosis of patients with liver failure at 90 days. Binary logistic regression analysis, as reported by Zhang et al [16] , revealed that cortisol level and MELD score were independent risk factors. Levels below this cut off were associated with increased mortality and morbidity, and this was similar to a study by Zhang et al [16] in which the cut-off values for the prediction of mortality were identified for cortisol levels (252.3 nmol/L equal to 105 ng\dl).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the current research, prolactin and cortisol levels were an independent risk factor, while PV Diameter, MELD score, Child Score, and Ascities were independent variables impacting the prognosis of patients with liver failure at 90 days. Binary logistic regression analysis, as reported by Zhang et al [16] , revealed that cortisol level and MELD score were independent risk factors. Levels below this cut off were associated with increased mortality and morbidity, and this was similar to a study by Zhang et al [16] in which the cut-off values for the prediction of mortality were identified for cortisol levels (252.3 nmol/L equal to 105 ng\dl).…”
Section: Discussionmentioning
confidence: 70%
“…Binary logistic regression analysis, as reported by Zhang et al [16] , revealed that cortisol level and MELD score were independent risk factors. Levels below this cut off were associated with increased mortality and morbidity, and this was similar to a study by Zhang et al [16] in which the cut-off values for the prediction of mortality were identified for cortisol levels (252.3 nmol/L equal to 105 ng\dl). In this study, the sensitivity and specificity for mortality based on cortisol AM level cut off 40ng/dl was 92,80, and the sensitivity and specificity for mortality based on cortisol PM level cut off 25 ng/dl was 88,80, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, our study found a significant moderate negative correlation between cortisol levels and bilirubin levels at visit 1 and visit 2, but a significant positive correlation at visit 3 (Figure 9), although bilirubin levels were within a healthy range. This relationship may warrant further study since cortisol levels have been negatively associated with chronic liver disease and depression is common in such patients [69,70]. Regarding α-amylase, a negative correlation with both total protein and total cholesterol was evident at visit 2, but not at visit 1 and visit 3 (Figure 9).…”
Section: Biomarkers Of General Health and Well-beingmentioning
confidence: 93%